A new putative species in the Ectatomma ruidum complex (Formicidae: Ectatomminae) produces a species-specific distress call. Issue 3 (4th May 2022) - Peña Carrillo, Kenzy I.; Lorenzi, María Cristina; Brault, Maxence; Devienne, Paul; Lachaud, Jean-Paul; Pavan, Gianni; Poteaux, Chantal
ABSTRACT: Social insects communicate by using chemical, visual, tactile, and acoustic signals, including stridulations. Ectatomma ruidum is a mainly Neotropical ant species complex that has faced strong divergence at the genetic level; the species have a highly variable blend of cuticular hydrocarbons and a relatively conserved morphology. Based on evidence for genetic and chemical differentiation, we tested for variation in acoustic traits. We compared the stridulations produced by the species E. ruidum sp. 2, sp. 3–4 and the new putative species E. ruidum sp. 5, as well as the morphology of the stridulatory file. We found that the stridulations produced by E. ruidum sp. 5 were statistically different from those of the other species in a number of traits. The differences in stridulatory traits might rely more on the way the ants produce the sound (rubbed area percentages) than on the morphology of the stridulatory file, for which we did not find variation. Our results highlight the use of acoustic traits as potential taxonomic tools for integrative taxonomic studies and suggest that the acoustic traits of E. ruidum species complex have been subjected to selection.